The Role Of Government And Community In Realizing Socially Entrepreneurial Village-Owned Enterprises (Bum Desa) - Ngurah Wisnu Murthi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The aim of this research is to 1) examine the development of (VOE) (BUM DESA), and 2) examine the role of government, society and social entrepreneurs in the growth of BUM DESA. This research is a qualitative descriptive study that will use a convenience sampling approach with a sample of BUM DESA formed in coastal villages. Data for 2022 shows the government's involvement in building BUM DESA in the form of provincial and/or district government representatives carrying out outreach and awareness to village communities about the relevance of BUM DESA for improving community welfare. The task of the village government is to motivate, educate and prepare the community to develop their own lives. In this situation, the village government provides assistance in the form of education and training, as well as other forms of fulfillment that can help establish BUM DESA. 2) The manifestation of the community's role in developing BUM DESA, namely community involvement, has also been seen in the form of socialization, both directly and indirectly, but not yet comprehensively, only some communities, and many communities have also been involved. involved in programs that have been implemented by BUM DESAa. Community participation can be seen from the decision-making stage, implementation stage, and utilization of results until evaluation is already in place, although not yet optimal, such as at the planning and evaluation stages where community participation is still only indirect. participation or through representatives. 3) This research found a lot of social entrepreneurship as shown by the collaboration index and creativity of BUM DESA administrators in developing BUM DESA. This research provides the following recommendations: 1) The government in collaboration with institutions should provide BUM DESA management training so that BUM DESA businesses can develop and be better able to improve the welfare of village communities. 2) BUM DESA administrators and village governments must strengthen their ability to identify potential in villages in order to further diversify businesses. 3) The government in collaboration with universities should provide BUM DESA management training, especially for BUM DESA managers so that they can apply the principles of social entrepreneurship in the educational curriculum or through business incubators and local government training courses.